(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Objectives: This study aimed to systematically evaluate the efficacy and safety of Eye Mantra Drops, a modern formulation integrating ayurvedic principles and medicinal plant extracts, in addressing various ocular conditions, including conjunctivitis, iritis, dry eyes, eye strain, itchiness, and watery eyes. Methods: The study adopted a single-center, open-label, non-randomized, post-marketing surveillance approach, involving 120 subjects with diverse ocular conditions. Eye Mantra Drops, comprising thirteen traditionally used ingredients, were administered to the participants for 7 days. Frequency and severity of symptoms, vital signs, and adverse events were assessed at screening and at the end of study to evaluate the safety and efficacy of Eye Mantra Drops. Results: The study revealed a significant reduction in frequency and symptom severity across diverse ocular conditions, including conjunctivitis, iritis, dry eyes, itchiness, watery eyes, and eye strain. No adverse events were reported, and vital signs remained stable, indicating the safety of Eye Mantra Drops. Conclusion: Eye Mantra Drops emerged as a promising and well-tolerated intervention for various ocular conditions including conjunctivitis, iritis, dry eyes, eye strain, itchiness, and watery eyes.